Using distance patron data to improve library services and cross-campus collaboration - Pitts, Joelle; Coleman, Jason; Bonella, Laura J. (My University, 2013)
This article discusses the data-driven activities of Kansas State University Libraries in response to documented lack of awareness and usage of library resources within our distance community. It presents data from a survey distributed to our distance education students and faculty, and concludes that because distance patrons are largely unaware of library services, targeted promotional efforts must be implemented and systematically reviewed. These efforts, and several new resources, are discussed in detail. While developed and targeted to distance patrons, each initiative also allowed for increased library awareness and usage by an ever-growing on-campus population wishing to utilize library resources remotely.
Keywords: Distance education; Academic libraries; Promotion; Universal design; Use studies; Outreach